Pemphigoid Gestationis in a Third Trimester Pregnancy - Şenol Şentürk; Nursel Dilek; Yeşim Bayoğlu Tekin; Sabri Çolak; Betül Gündoğdu; Emine Seda Güvendağ Güven (Hindawi Limited, 2014)
Pemphigoid gestationis (PG) is a rare vesiculobullous dermatosis of pregnancy. It is commonly seen in second or third trimester. The diagnosis is frequently made with direct immunofluorescence studies of perilesional skin. Prompt recognition and appropriate management may reduce morbidity of this disease. Herein we present a case of pemphigoid gestationis occurring in a 33-year-old primigravida woman with symptoms of generalized pruritus.